Sax Island : Crime Time Comix : Eric Metcalfe - Hank Bull. (Vancouver : Western Front, 1983)
Design: Jane Ellison, Hank Bull, Eric Metcalfe ; Production: Jane Ellison ; Drawings: Eric Metcalfe ; Photographs taken on the set of the video production: David Hlynsky
Engels
boek
Keywords: Metcalfe, Eric; Bull, Hank